Effect of planting density and irrigation scheduling on Dry matter production,yield attributes and yield of Rabi maize (Zea mays L.) - Divya Singh,; Rajesh Kumar,; Abhinandan Singh,; Abhinav Kumar,; Alok Kumar Pandey,; Atish Yadav,; Neeraj Kumar, (The Bioscan, 2025)
A field experiment was conducted during rabi season of 2022-23 and 2023-24 to study the effect of planting density and irrigation scheduling on dry matter accumulation, yield attributes and yield of Rabi maize. Higher drymatter accumulation was recorded under highest plant population of 1,00,000 plants/ha , which was significant when compared to rest of the population at 60,90 and 120 DAS and at harvest during both the seasons and higher dry matter accumulation was recorded under irrigation scheduling of 25% Available soil moisture depletion and it decreased with decreasing moisture availability under different treatment while the lowest under 75% ASMD at all the stages of crop during both the seasons. Yield-contributing characteristics such as the no. of cobs per plant, cob length (cm), no. of grain rows, per cob, no. of grains, per cob, cob weight (g), and shelling percentage were significantly higher with planting density of (66,666 plants ha⁻¹) and irrigation scheduling at 25 % Available soil moisture deficit And grain and straw yield was recorded significantly higher under cropping density of 83,333 plants/ha with irrigation scheduling at 25% Available soil moisture deficit.